Maritime logistics a complete guide to effective shipping and port management - Song, Dong-Wook; Panayides, Photis M. (Kogan Page, 2012)
Current globalization and borderless operations in manufacturing are creating a greater demand for international transportation and supply chain logistics. Maritime (shipping and ports) is one of the key components in this business pattern. It is now estimated that approximately 90% of global trading freight moves by ship. As this trade increases it is becoming more important to have a clear understanding of the way in which freight is transported by sea and the role of ports in this exchange. This book covers many topics including shipping lines, container tankers, dry bulk, and port-centric logistics. Written by a team of international authors, who provide a truly global perspective on this increasingly key area of logistics, Maritime Logistics is a helpful, up-to-date resource for students of logistics and logistics professionals.